How to implement sustainability through culture at an European level (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
Culture is what brings us together while other forces threaten to drive us apart. The gravity of the COVID-19 pandemic proved that culture is a pillar to building cohesive, equal, free and sustainable societies.